Airport arrivals screening during pandemic (H1N1) 2009 influenza in New South Wales, Australia. Issue 5 (17th March 2014) - Gunaratnam, Praveena J; Tobin, Sean; Seale, Holly; Marich, Andrew; McAnulty, Jeremy
Abstract: Objective: To examine the effectiveness of airport screening in New South Wales during pandemic (H1N1) 2009 influenza. Design, setting and participants: Analysis of data collected at clinics held at Sydney Airport, and of all notified cases of influenza A(H1N1)pdm09, between 28 April 2009 and 18 June 2009. Main outcome measures: Case detection rate per 100 000 passengers screened, sensitivity, positive predictive value and specificity of airport screening. The proportion of all cases in the period detected at airport clinics was compared with the proportion detected in emergency departments and general practice. Results: Of an estimated 625 147 passenger arrivals at Sydney Airport during the period, 5845 (0.93%) were identified as being symptomatic or febrile, and three of 5845 were subsequently confirmed to have influenza A(H1N1)pdm09, resulting in a detection rate of 0.05 per 10 000 screened (95% CI, 0.02–1.14 per 10 000). Forty‐five patients with overseas‐acquired influenza A(H1N1)pdm09 in NSW would have probably passed through the airport during this time, giving airport screening a sensitivity of 6.67% (95% CI, 1.40%–18.27%). Positive predictive value was 0.05% (95% CI, 0.02%–0.15%) and specificity 99.10% (95% CI, 99.00%–100.00%). Of the 557 confirmed cases across NSW during the period, 290 (52.1%) were detected at emergency departments and 135 (24.2%) at general practices, compared with three (0.5%) detected at the airport. Conclusions: Airport screening was ineffective in detecting cases of influenza A(H1N1)pdm09 in NSW. Its future use should be carefully considered against potentially more effective interventions, such as contact tracing in the community.